Предмет: Математика,
автор: darklayn307
please help
с решением
Приложения:
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
( a + 2 ) ( b + 2 )
= a ( b + 2 ) + 2 ( b + 2 )
= ab + 2a + 2b + 4
( a - 2 ) ( b - 2 )
= a ( b - 2 ) - 2 ( b - 2 )
= ab - 2a - 2b + 4
( a - 2 ) ( b + 2 ) - ( a - 2 ) ( b - 2 )
= ab + 2a + 2b + 4 - ( ab - 2a - 2b + 4 )
= ab + 2a + 2b + 4 - ab + 2a + 2b - 4
= ab - ab + 2a + 2a + 2b + 2b + 4 - 4
= 0 + 4a + 4b + 0
= 4a + 4b
Похожие вопросы
Предмет: Русский язык,
автор: СуперДенис
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: Лера123111111
Предмет: Математика,
автор: dilya1990
Предмет: Алгебра,
автор: pandaminimi